Hubungan Perilaku Jajan Dengan Kejadian Diare Pada Anak Sekolah Dasar: Di Kel. Cempaka Kec. Cempaka Kota Banjarbaru - Aditya Pradipta Hernanda; Djallalluddin Djallalluddin; Meitria Syahadatina Noor (Berkala Kedokteran, 2013)
ABSTRACT: Diarrheal disease in young children seems increasingly common in many topycal countries,especially in urban areas were dirty and crowded. Until now diarrhea is still one of the major health problem of the community in Indonesia.Diarrhea is always in the order of 3 greater than 10 diseases most health centers. The magnitude of the problem is evident from the high rate of mordibity and mortality due to diarrhea. The design of the study is observational analytic study. This research was conducted with a cross sectional study. From the research group hygienic respondents, 20 students (34.5%) suffered from diarrhea and as many as 38 students (63.5%) did not have diarrhea. Looking at the group of respondents unhygienic, as many as 98 students (78.4%) suffered from diarrhea and only 27 students (21.6%) who did not have diarrhea. The correlation test was used chi-square analysis because the variables have the habit of eating snacks nominal scale data form. Results obtained value of p = 0.000, this result is smaller than the value of a = 0.05. It means there is a significant relationship between the habit of eating snacks with diarrhea. The incidence of diarrhea largely categorized by 65.5% suffered from diarrhea. Figures hygiene most unhygienic categorized by 68.7% There is a significant association with the incidence of diarrhea snack behavior. Keywords: diarrhea, snack behavior, hygienic ABSTRAK      : Penyakit diare pada anak usia muda tampaknya makin sering dijumpai di berbagai negara tropis, khususnya di daerah perkotaan yang kotor dan padat. Sampai saat ini penyakit diare masih merupakan salah satu masalah kesehatan utama dari masyarakat di Indonesia. Diare selalu masuk dalam urutan 3 besar dari 10 penyakit terbanyak  Puskesmas. Besarnya masalah tersebut terlihat dari tingginya angka kesakitan dan kematian akibat diare. Rancangan penelitian yang digunakan adalah penelitian observasional analitik. Penelitian ini dilakukan dengan pendekatan cross sectional. Dari hasil penelitian kelompok responden yang higienis, sebanyak 20 siswa (34,5%) menderita diare dan sebanyak 38 siswa (63,5%) tidak menderita diare. Sedang pada kelompok responden tidak higienis, sebanyak 98 siswa (78,4%) menderita diare dan hanya 27 siswa (21,6%) yang tidak menderita diare. Adapun uji korelasi pada analisa ini digunakan Chi Square karena variabel kebiasaan jajan mempunyai bentuk data berskala nominal. Hasil yang didapatkan nilai p = 0,000, hasil ini ternyata lebih kecil dari nilai a = 0,05. Hal ini dapat diartikan terdapat hubungan yang signifikan antara kebiasaan jajan dengan kejadian diare. Angka kejadian diare sebagian besar dikategorikan menderita diare sebesar 65,5%. Angka higienitas sebagian besar dikategorikan tidak higienis sebesar 68,7% Ada hubungan yang bermakna perilaku jajan dengan kejadian diare  Kata kata kunci : kejadian diare, perilaku jajan, higienis.